2000
DOI: 10.1007/s002689910007
|View full text |Cite
|
Sign up to set email alerts
|

Relaparotomy in Peritonitis: Prognosis and Treatment of Patients with Persisting Intraabdominal Infection

Abstract: Some patients are prone to persisting intraabdominal infection regardless of initial eradication of the source of infection. Our aim was to characterize patients who had to undergo relaparotomy for persisting abdominal sepsis using simple clinical parameters and to define those patients who are susceptible to benefit of aggressive surgical treatment by early and repeated reoperations to control multiple organ dysfunction syndrome (MODS) caused by ongoing intraabdominal infection. Persisting abdominal sepsis wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
126
4
20

Year Published

2001
2001
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 201 publications
(153 citation statements)
references
References 34 publications
3
126
4
20
Order By: Relevance
“…13,14 In actual MPI score predicts higher mortality rate (26%) in both survivors as well as in non survivors as compared to APACHE II score (15% A prediction accuracy of 84-90% has been reported for APACHE in the previous studies. [15][16][17] Dino et al in their study had reported sensitivity, specificity, positive predictive value and negative predictive value of APACHE as 82.5%, 54.7%, 82.8%, 66% respectively. In present study APACHE II is more specific than MPI in prediction of mortality.…”
Section: Discussionmentioning
confidence: 99%
“…13,14 In actual MPI score predicts higher mortality rate (26%) in both survivors as well as in non survivors as compared to APACHE II score (15% A prediction accuracy of 84-90% has been reported for APACHE in the previous studies. [15][16][17] Dino et al in their study had reported sensitivity, specificity, positive predictive value and negative predictive value of APACHE as 82.5%, 54.7%, 82.8%, 66% respectively. In present study APACHE II is more specific than MPI in prediction of mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies comparing the two strategies in patients with secondary peritonitis revealed a significant advantage for patients treated by the on demand strategy as measured by mortality and complication rate [2,5,21,23]. Exceptions include patients with intestinal ischemia, advanced tertiary peritonitis, infected ascites, or those who need to have a reestablishment of intestinal continuity at a second operation [8].…”
Section: Discussionmentioning
confidence: 99%
“…The surgeon should make the diagnosis within the first 48 hours after any of these nonspecific findings occur and avoid waiting until the fifth or seventh postoperative day, even though some authors suggest that anastomotic failure or leaks may take that long to manifest themselves. Koperna and Schulz [86] showed that patients reoperated after 48 hours had mortality significantly higher than those operated earlier (76.5% versus 28%; P = .001); however, the timing of the relaparotomy did not have any repercussion on survival in those patients who had an acute physiology and chronic health (APACHE) II score greater than 26. This finding suggested that under these circumstances of severely impaired physiology the early operation had little effect.…”
Section: Re-laparotomy "On Demand"mentioning
confidence: 99%